1996
DOI: 10.1161/01.res.78.1.137
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ischemic Preconditioning of the Myocardium on cAMP

Abstract: Reduction of cAMP has been implicated in the protection of ischemic preconditioning (IP), but until now, this possibility has not been directly addressed. In this study, we found that in the in vivo rabbit heart 10 to 30 minutes of sustained regional ischemia was accompanied by a nearly twofold rise in cAMP levels. This increase in cAMP was attenuated when sustained ischemia was preceded by IP induced with a single cycle of transient ischemia and reperfusion (TI/R) and prevented when ischemia was preceded by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 27 publications
3
20
1
Order By: Relevance
“…Glucose liberated from glycogen degradation exits lysosomes via the lysosomal membrane glucose carrier (55). The glycogen hydrolyzing activity of acid ␣-glucosidase is enhanced by Ca 2ϩ , which in the setting of increased cytosolic Ca 2ϩ in the ischemic myocardium, in concert with cAMP-mediated augmented lysosomal Ca 2ϩ uptake, may prime lysosomes for accelerated glycogen degradation (41,79). There is strong evidence from glycogen storage diseases that autophagic/lysosomal glycogen breakdown is important for maintaining normal cardiac glycogen levels and does not simply constitute a redundant alternative breakdown route for glycogen (68).…”
Section: )mentioning
confidence: 99%
“…Glucose liberated from glycogen degradation exits lysosomes via the lysosomal membrane glucose carrier (55). The glycogen hydrolyzing activity of acid ␣-glucosidase is enhanced by Ca 2ϩ , which in the setting of increased cytosolic Ca 2ϩ in the ischemic myocardium, in concert with cAMP-mediated augmented lysosomal Ca 2ϩ uptake, may prime lysosomes for accelerated glycogen degradation (41,79). There is strong evidence from glycogen storage diseases that autophagic/lysosomal glycogen breakdown is important for maintaining normal cardiac glycogen levels and does not simply constitute a redundant alternative breakdown route for glycogen (68).…”
Section: )mentioning
confidence: 99%
“…However, more studies might be expected to clarify these issues. On the other hand, IP leads to decreased cAMP accumulation during sustained ischemia, 22 but it is controversial whether this explains the cardioprotection afforded by preischemic activation of PKA. 5,22 Enhancement of cAMP accumulation during sustained ischemia fails to block cardioprotection by IP.…”
Section: Circulation July 6 2004mentioning
confidence: 99%
“…On the other hand, IP leads to decreased cAMP accumulation during sustained ischemia, 22 but it is controversial whether this explains the cardioprotection afforded by preischemic activation of PKA. 5,22 Enhancement of cAMP accumulation during sustained ischemia fails to block cardioprotection by IP. 22 Moreover, overexpression of ␤-adrenergic receptor kinase-1, which causes functional uncoupling of ␤-adrenoceptors, impairs ischemia-reperfusion injury, and this impairment is reversed by co-overexpression of ␤-adrenergic receptor kinase-1 inhibitor.…”
Section: Circulation July 6 2004mentioning
confidence: 99%
See 1 more Smart Citation
“…Involvement of the ␤-adrenergic signal transduction pathway in preconditioning has recently been suggested: we 4 and others 5,6 have shown that preconditioning attenuates cAMP generation during sustained ischemia in rat and rabbit myocardium. Sandhu et al 5 proposed reduced stimulation of the ␤-adrenergic receptor secondary to reduced release of norepinephrine 7 rather than desensitization as an explanation.…”
mentioning
confidence: 94%